2016
DOI: 10.1016/j.clinbiomech.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a knee brace intervention on perceived pain and patellofemoral loading in recreational athletes

Abstract: 23Background: The current investigation aimed to investigate the effects of an intervention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
(1 reference statement)
2
18
0
Order By: Relevance
“…Knee braces aim to improve the tracking of the patella in the trochlea grove (Paluska & McKeag, 2000). The use of proprioceptive bracing in injury prevention has also attracted some attention during daily activities (Selfe et al, 2011) and sports specific tasks (Hanzlíková et al, 2016; Sinclair et al, 2016; Sinclair, Vincent & Richards, 2017); however, little is known about their efficacy when the athlete is in a fatigued state. The aim of this study was to determine the changes in knee kinetics and kinematics during badminton lunges to the net due to; fatigue, lunge direction (forehand and backhand) and knee bracing.…”
Section: Introductionmentioning
confidence: 99%
“…Knee braces aim to improve the tracking of the patella in the trochlea grove (Paluska & McKeag, 2000). The use of proprioceptive bracing in injury prevention has also attracted some attention during daily activities (Selfe et al, 2011) and sports specific tasks (Hanzlíková et al, 2016; Sinclair et al, 2016; Sinclair, Vincent & Richards, 2017); however, little is known about their efficacy when the athlete is in a fatigued state. The aim of this study was to determine the changes in knee kinetics and kinematics during badminton lunges to the net due to; fatigue, lunge direction (forehand and backhand) and knee bracing.…”
Section: Introductionmentioning
confidence: 99%
“…Patellofemoral bracing has been shown to provide short term benefits in pain and functional activities such as walking and squatting. [39][40][41]. Postulated mechanisms of pain relief in addition to improved patellar tracking include unloading of the extensor mechanism, increased temperature and proprioception, or improved confidence.…”
Section: Patellofemoral Painmentioning
confidence: 99%
“…Unfortunately, the effects diminished at long-term (52 weeks) follow-up [42]. Bracing has been shown to be a good short-term treatment for pain [39][40][41][42], but much like taping has not shown significant longterm effects. Despite this, one should consider bracing as adjunctive therapy as they are low cost, safe, and able to provide patients short-term benefit to pain and functional activities.…”
Section: Patellofemoral Painmentioning
confidence: 99%
“…Passive interventions are relatively inexpensive and can be applied during sport and recreational activities [19][20][21][22]. Furthermore, a knee brace can be applied by the user without assistance from a healthcare professional and thereby can give the patient more control over the management of their PFP [23]. Several studies reported that knee braces have modified the frontal and transverse plane motion of the knee joint [24][25][26].…”
Section: Introductionmentioning
confidence: 99%